Hypertensive and Non-hypertensive Hospital Admission Blood Pressure Association with Cognitive Function in Stroke Patients - Rifqi, Muhammad Andika; Setyowatie, Sita; Putranto, Johanes Nugroho Eko (Universitas Airlangga, 2024)
Highlight: A comparative study of hypertension and non-hypertension on cognitive function. Hospital admission blood pressure and cognitive function in acute-phase stroke patients. Blood pressure is not associated with cognitive function. ABSTRACT Introduction: Cognitive impairment is one of the many stroke effects. White matter damage, microinfarcts, microbleeding, atrophy, and amyloid buildup in the brain due to stroke are all potential causes of this condition. Cognitive impairment studies have yet to provide a definitive explanation for how this condition develops following a stroke. Blood pressure is one of several risk factors for stroke. Meanwhile, few studies have been conducted on the association between blood pressure and cognitive function in stroke patients, and no definitive results have been established. Objective: This research was designed to examine and evaluate the difference in the measured cognitive function category between hypertensive and non-hypertensive hospital admission blood pressure stroke patients. Methods: This research used a cross-sectional design with a consecutive sampling method on acute stroke patients at Dr. Soetomo General Academic Hospital. The MMSE (Mini Mental State Examination) was carried out to assess the degree of cognitive function. The blood pressure measured is the hospital admission blood pressure. Results: There were 40 patients included in this study. A total of 36 patients (90%) were in the hypertension group (blood pressure â‰¥ 130/80 mmHg), and 4 patients (10%) were in the non-hypertension group (blood pressure < 130/80 mmHg). The MMSE results showed that 10 patients performed with no cognitive impairment, 12 patients performed with mild cognitive impairment, and 18 patients performed with severe cognitive impairment. Statistical analysis of the Mann-Whitney U test showed that p = 0.561. Conclusion: There was no difference in the measured cognitive function category between hypertensive and non-hypertensive hospital admission blood pressure stroke patients.